2018
DOI: 10.1007/s00167-018-4994-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparable clinical and structural outcomes after arthroscopic rotator cuff repair in diabetic and non-diabetic patients

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“… 2 Several clinical studies have further investigated the relationship between DM and retearing of the rotator cuff tendon. 5 , 9 11 , 14 Some clinical studies have reported significantly higher retear rates of repaired rotator cuff tendon in patients with DM. 5 , 10 However, the findings of other studies have not supported DM as a risk factor for tendon retear after arthroscopic rotator cuff repair.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Several clinical studies have further investigated the relationship between DM and retearing of the rotator cuff tendon. 5 , 9 11 , 14 Some clinical studies have reported significantly higher retear rates of repaired rotator cuff tendon in patients with DM. 5 , 10 However, the findings of other studies have not supported DM as a risk factor for tendon retear after arthroscopic rotator cuff repair.…”
mentioning
confidence: 99%
“… 5 , 10 However, the findings of other studies have not supported DM as a risk factor for tendon retear after arthroscopic rotator cuff repair. 9 , 11 , 14 …”
mentioning
confidence: 99%
“…This meta-analysis showed that diabetes was significantly associated with an increased risk of retears in patients after rotator cuff repair, with no heterogeneity found across the included studies. Subgroup analysis of 2 studies 18,51 found that the retear rate was negatively correlated with blood glucose control. In most groups, the diabetic group had worse clinical outcomes after rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous studies have compared the clinical scores of rotator cuff repair between patients with and without diabetes and showed that there were no significant differences between the groups at final followup. 18,20,51 In addition, Clement et al 20 found that the mean improvement in pre-to postoperative outcome scores was significantly greater (P ¼ .0002) in patients without diabetes compared with those with diabetes. This indicates that the impact of diabetes on outcome scores is uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation